Noninvasive testing in the management of children with suspected inflammatory bowel disease. (4th May 2019) - Dilillo, Dario; Zuccotti, Gian Vincenzo; Galli, Erica; Meneghin, Fabio; Dell'Era, Alessandra; Penagini, Francesca; Colella, Giacomo; Lewindon, Peter; Carmagnola, Stefania; Farina, Elisa; Ardizzone, Sandro; Maconi, Giovanni
Abstract: Objective: To assess the accuracy of noninvasive parameters, fecal calprotectin (FC), increased bowel wall thickening (BWT) at intestinal ultrasound (IUS) and blood inflammatory indexes (BII), alone or in combination, as diagnostic tools for inflammatory bowel disease (IBD) in pediatric patients. Methods: Retrospective data were collected on consecutive children (age 2–18 years) referred to our pediatric gastroenterology clinic, for recurrent abdominal pain and/or altered bowel habit from 2007 to 2013. Subjects who had diagnostic workup: laboratory tests (FC, BII, white blood cell (WBC), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR)) and IUS as initial assessment were eligible. Subjects with known gastrointestinal (GI) diseases, or signs or symptoms highly suggestive for organic diseases necessitating prompt endoscopy (e.g., perianal disease or rectal bleeding), or who had recently performed endoscopy were excluded. The accuracy of noninvasive tests for detecting IBD was assessed using endoscopic and/or radiological investigations, performed in subsequent clinical follow up, as reference gold standard. Results: Seventy-seven patients (mean age 11.3, 44 males) were included, 23 (29.9%) with a final diagnosis of IBD. As single tests, FC gave the highest sensitivity (96%) but lower specificity (72%) and IUS highest specificity (96%) with lower sensitivity (70%). The combination of FC + IUS showed excellent accuracy for detecting children with IBD with positive predictive value: 100%; negative predictive value: 88.5%. The probability of IBD in children with normal FC, BII and IUS was 0.09%. Conclusions: FC and increased BWT at IUS are accurate to guide reassurance or proceeding with further invasive procedures for detecting IBD in children with mild GI symptoms.